Reestructuración técnico administrativa de la empresa Plastic GyD (2019)
The technical and administrative restructuring of the company Plastic GyD, had as its purpose the implementation of the basic concepts of industrial engineering, where internal and external factors were analyzed to the company Plastic GyD, in order to propose integral solutions at operational and administrative level , the financial indicators allowed to sustain the feasibility, viability and profitability of the project.